1997
DOI: 10.11130/jei.1997.12.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Relative Price Dispersion and the Rate of Inflation: The Evidence from Japan

Abstract: The relationship between inflation and price variability has been of interest to economists for many years. Recently, Ball and Mankiw [1995] have proposed a menu-cost model of price stickiness in which the skewness of relative price inflation matters as well as the standard deviation. In this paper their model is tested on Japanese wholesale price data. The results are mixed. When we use the single equation approach of Ball and Mankiw the results appear to favour their model. However, once we condition inflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In literature large, a number of empirical studies have provided evidence in favour of positive relationship between the skewness of the cross-sectional distribution of relative price changes and the aggregate inflation (see, for example, Amano & Macklem, 1997; Assarsson, 2003; Aucremanne et al, 2002; Ball & Mankiw, 1995; Dopke & Pierdzioch, 2000). 3 These results stand in contrast to the findings of Holly (1997) who finds that the skewness of the distribution of relative price changes does not exert a strong impact on the average inflation rate. More recently, Pou and Dabus (2008), extending the literature on this relationship, found that inflation and skewness relationship depends on the inflationary history of the country and thus may vary across countries.…”
Section: Introductionmentioning
confidence: 76%
“…In literature large, a number of empirical studies have provided evidence in favour of positive relationship between the skewness of the cross-sectional distribution of relative price changes and the aggregate inflation (see, for example, Amano & Macklem, 1997; Assarsson, 2003; Aucremanne et al, 2002; Ball & Mankiw, 1995; Dopke & Pierdzioch, 2000). 3 These results stand in contrast to the findings of Holly (1997) who finds that the skewness of the distribution of relative price changes does not exert a strong impact on the average inflation rate. More recently, Pou and Dabus (2008), extending the literature on this relationship, found that inflation and skewness relationship depends on the inflationary history of the country and thus may vary across countries.…”
Section: Introductionmentioning
confidence: 76%
“…Gerlach and Kugler (2007 confirm that finding for the period 1981-1986 using the method of a random cross-section sample split to address the small sample issue pointed out by Bryan and Cecchetti (1999). Finally, Holly (1997) controls for the growth Figure 1: CPI inflation rate for Japan (1999.01-2009.12) Quantitative Easing Period in money and rejects the Ball and Mankiw (1995) hypothesis, based on Japanese wholesale price data for 1976-1994.…”
Section: Introductionmentioning
confidence: 79%
“…However, some studies have found more ambiguous effects (see, for example, Hall and Yates (1998), for the UK; Raftai (2004) for Hungary and Pou and Dabús (2005) for Spain and Argentina). More skeptical commentators include Holly (1997), who uses Japanese data to argue that causation runs from aggregate inflation to the distribution of relative price changes, and not vice versa and Bryan and Cecchetti (1999), who argue that the relationships estimated in the literature reflect measurement error (but see the rejoinder by Ball and Mankiw, 1999). It has also been suggested that a relationship based on menu-cost arguments is not be applicable in a context of a higher inflation rate where menu costs are less relevant.…”
Section: Methodsmentioning
confidence: 99%